Factors influencing the purchase intention on social commerce platforms among undergraduates students at the Faculty of Entrepreneurship and Business, Universiti Malaysia Kelantan - Muhammad Afieq Amrie Mazlan; Nur Afiqah Amira Roslee; Nurul Syahran Rosli; Tan Chee Wei (2024)
In the last ten years, the emergence of smartphones, applications, and social networking sites has resulted in the growth of social commerce, which is an innovative way for businesses and people to engage on a trade. The social commerce trend mostly relies on the exchange of information and social connections, and how these influence peoples' intention to make purchases. The research intended at exploring the influence of social commerce on purchase intention among undergraduates’ students at the Faculty of Entrepreneurship and Business, Universiti Malaysia Kelantan. The study examined several independent variables, namely perceived usefulness, perceived easy of use, perceived risk, and perceived enjoyment. This study applied a descriptive methodology; 353 students from UMK Campus Kota participated in it via a Google Form questionnaire utilising a Likert scale. In this study, PSS is employed to analyse the gathered data. Result found that Spearman’s correlation value of perceived usefulness, perceived ease of use, and perceived enjoyment had positive significant relationship. While perceived risk was negatively significant on Purchase intention in social commerce. Finally, the study thoroughly examined its implications, limitations, and recommendations for further research.